2010
DOI: 10.2147/ijgm.s3495
|View full text |Cite
|
Sign up to set email alerts
|

Update on transfusion solutions during surgery: review of hydroxyethyl starches 130/0.4

Abstract: ObjectivesRestoration of circulation is crucial in the surgical patient management. Colloids and crystalloids are widely used for blood volume therapy. We reviewed recent trials to evaluate efficacy and safety of hydroxyethyl starch (HES) 130/0.4 during surgery.Material and methodsA subjective, not systematic, review of literature was performed. Papers were searched to answer questions about efficacy of HES, its impact on coagulation and inflammation and its effects on pulmonary mechanics and renal function.Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…5 Modern generation low-molecular-weight hydroxyethyl starch solutions have been shown to be less likely to induce nephrotoxicity and coagulopathy. 6 However, the use of hydroxyethyl starch, including low-molecular-weight hydroxyethyl starch, has significantly decreased recently because of inconclusive evidence in several studies in intensive care patients. [7][8][9][10] However, there are no prospective studies presenting harm of synthetic colloids in surgical patients.…”
Section: Discussionmentioning
confidence: 99%
“…5 Modern generation low-molecular-weight hydroxyethyl starch solutions have been shown to be less likely to induce nephrotoxicity and coagulopathy. 6 However, the use of hydroxyethyl starch, including low-molecular-weight hydroxyethyl starch, has significantly decreased recently because of inconclusive evidence in several studies in intensive care patients. [7][8][9][10] However, there are no prospective studies presenting harm of synthetic colloids in surgical patients.…”
Section: Discussionmentioning
confidence: 99%
“…HES, especially the older molecules, might be a factor of renal function worsening and should probably be avoided. However, it is worthy of note that even in recent reviews, there is still no definitive evidence of an association between HES administration and worsening of renal function (15–17). Anyway, only one patient received HES in our series.…”
Section: Discussionmentioning
confidence: 99%
“…This is further supported by the fact that when noncolloidal low‐volume resuscitation agents, such as hypertonic saline (HTS), were included in the studies, they were found to produce similar pulmonary protective effects as HES . Clinical studies on major vascular surgery in people, in which pulmonary edema is a significant problem, have not endorsed findings of positive protective effects of HES . Similar studies have not been undertaken in veterinary medicine and possible effects of HES on pulmonary vasculature in spontaneous disease in dogs and cats remain speculative.…”
Section: Hes Has Pulmonary Protective Effectsmentioning
confidence: 99%
“…The major concerns in the use of any colloid include anaphylactic reactions, coagulopathies, tissue accumulation, renal failure, and increased mortality . Although HES 130/0.4 is associated with adverse effects, human reviews and meta‐analyses incorporating results from studies on small populations of healthy volunteers to large randomized phase II to IV trials, generally report an overall safer profile compared to its predecessors . These conclusions suggest that when it comes to choosing a colloidal product, tetrastarch may be the least detrimental but this does not necessarily imply that it should be chosen before crystalloids.…”
Section: Hes Has An Improved Risk/benefit Profilementioning
confidence: 99%